The Effect of External Magnetic Field on Microstructure and Magnetic Properties of Melt-Spun Nd-Fe-B/Fe-Co Nanocomposite Ribbons - Xuan Truong Nguyen; Hong Ky Vu; Hung Manh Do; Van Khanh Nguyen; Van Vuong Nguyen (Advances in Materials Science and Engineering)
The ribbons Nd2Fe14B/Fe-Co were prepared with the nominal composition Nd16Fe76B8/40% wt. Fe65Co35 by the conventional and the developed magnetic field-assisted melt-spinning (MFMS) techniques. Both ribbons are nanocomposites with the smooth single-phase-like magnetization loops. The 0.32 T magnetic field perpendicular to the wheel surface and assisting the melt-spinning process reduces the grain size inside the ribbon, increases the texture of the ribbon, improves the exchange coupling, and, in sequence, increases the energy product (BH)max of the isotropic powdered samples of MFMS ribbon in ~9% by comparison with that of the ribbon melt-spun conventionally. The grain size reduction effect caused by the assisted magnetic field has also been described quantitatively. The MFMS technique seems to be promising for producing high-performance nanocomposite ribbons.